A Turkish study of medical student learning styles. - (:unkn) unknown (My University, 2011)
A good understanding of the learning styles of students is necessary for optimizing the quality of the learning process. There are few studies in Turkey on the subject of the learning characteristics of medical students. The aim of this study was to define the learning patterns of Turkish medical students based on the Turkish version of Vermunts Inventory of Learning Styles (ILS). The Turkish version of the ILS was developed and administered to 532 medical students. Learning patterns were investigated using factor analysis. Internal consistencies of scales ranged from 0.43 to 0.80. The Turkish version of the ILS identified four learning styles among medical students. In comparing the pre-clinical and clinical phases of medical students related to mental models of learning, statistically significant differences (p < .01) were found between the two groups for the learning characteristics: lack of regulation; certificate; self-test and ambivalent orientation; intake of knowledge; and use of knowledge. The Turkish version of the ILS can be used to identify learning styles of medical students. Our findings indicate an intermediate position for our students on a teacher-regulated to student-regulated learning continuum. A variety of teaching methods and learning activities should be provided in medical schools in order to address the range of learning styles.